FRACTURE FAILURE ANALYSIS OF A AUTO HIGH STRENGTH ASSEMBLING BOLT - LAN XiuQiong; CHEN JianHua (Jixie qiangdu)
Cross section microstructure and fractography of a Auto high strength assembling bolt of 35 steel were observed by optical microscope（ OM） and electron scanning microscope（ SEM）. The hardness of the bolt was measured by HR-150A rockwell hardness tester. The fracture failure of the assembling bolt was analyzed. The results indicate that quenching and tempering treatment on the assembling bolt meet the national standard,but the strength was decreased by the quenching crack generated during quenching. The extension of quenching crack that due to the external force result in the fracture failure.